Changing Infrastructural Practices: Routine and Reproducibility in Automated Interdisciplinary Bioscience. (November 2020) - Meckin, Robert
Proponents of engineering and design approaches to biology aim to make interdisciplinary bioscience research faster and more reproducible. This paper outlines and deploys a practice-based approach to analyses of infrastructure that focuses on the routine epistemic activities and charts how two such routines are unsettled and resettled in the background of epistemic culture. This paper describes attempts to bring about new research infrastructures in synthetic biology using robotics and software-enabled design. A focus on the skills of pipetting shows how established manual labor has to be reconfigured to fit with novel robotic automations. An analysis of curating frozen materials shows that automated design presents new problems for the established activities of storing and retrieving biological materials. These movements, while transient, have implications for organizing interdisciplinary collaboration, research productivity, and enabling greater reproducibility. This paper explores the idea of infrastructure as practice and shows how this has important implications for studies of research infrastructures. This article discusses the main contributions of this approach for analysts of infrastructure in terms of movements, temporalities, and ethics and offers suggestions for what the research implies for synthetic biology.